Creatine supplementation. Its role in human performance - Kraemer, W. J.; Volek, J. S. (Clinics in Sports Medicine, 1999)
Creatine supplementation is the most popular nutritional supplement today. Although many questions remain regarding the use and benefits of creatine supplementation, a fast-growing body of literature is starting to define both its acute and chronic effects on human and physiologic performance. The initial data indicate that this energetic boost of the phosphagen energy system also helps to enhance strength and power training. Few documented side effects have been demonstrated in the medical and scientific literature, but further investigation is still required as to long-term use (i.e., beyond several months).